IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI PAUD PELANGI BUNDA KOTA METRO - Era Margaretha (AT-TAJDID, 2019)
Early childhood education (PAUD) Pelangi Bunda is one of the educational institutions that is very concerned about human resources, especially in an effort to prosper his life. Teachers as human resources are an important component in school organizations. The quality of human resources can be a support for the creation of quality education. However, quality human resources will not run as it should if it is not supported by sufficient financial. Therefore, Human Resources Management in PAUD Pelangi Bunda must be done well in order to improve the quality of education. learning motivation of learning citizens / communities.Keywords: Human Resource Management, Quality of Education